2016
DOI: 10.1016/j.medici.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals’ skills regarding patient safety

Abstract: This study has served to investigate the general skills of health care professionals in regard to patient safety. It provides new knowledge about the topic in the context of the Baltic countries and can thus be used in the future development of health care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…As regards to qualification and the current position, the current study results clarified that nearly the majority of studied nurses were secondary school graduate and the minority of them acted as head nurse. This finding is consistent with the study done by Brasaitė, Kaunonen ,Martinkėnas, Mockienė and Suominen, (2016), who explained that most of studied operating room nurses were medical school graduate and the main base-qualifications were a non-university bachelor. In addition, this is supported by Adejumo and Olatunji (2013) when they reported that above sixty percent of nurses had Diploma certificates .…”
Section: Discussionsupporting
confidence: 92%
“…As regards to qualification and the current position, the current study results clarified that nearly the majority of studied nurses were secondary school graduate and the minority of them acted as head nurse. This finding is consistent with the study done by Brasaitė, Kaunonen ,Martinkėnas, Mockienė and Suominen, (2016), who explained that most of studied operating room nurses were medical school graduate and the main base-qualifications were a non-university bachelor. In addition, this is supported by Adejumo and Olatunji (2013) when they reported that above sixty percent of nurses had Diploma certificates .…”
Section: Discussionsupporting
confidence: 92%
“…Technological progress and the development in many fields of science enforce stronger and lasting relationships between education and employment [33]. New nursing put this group of professionals in need to engagement in personal professional development [1,2]. The analysis of the research results showed that for all the levels of readiness for learning and development average results prevailed and the highest level of readiness for learning and development was presented by nurses in terms of: openness to changes in environment, self-evaluation of past educational development, and effectiveness of on-the-job training [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The development of nursing and the taking over of new functions by nurses have made nursing in many countries a more complex profession, allowing for high-quality patient care [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital managers and HCPs play a key role in improving patient safety (Brasaitė, Kaunonen, Martinkėnas, Mockienė, & Suominen, ; Hughes & Clancy, ; Parand, Dopson, Renz, & Vincent, ). To date studies examining patient participation have been conducted in developed countries and have only looked at the views of patients or HCPs and no qualitative study has included the perspective of policy makers (De Brun, Heavey, Waring, Dawson, & Scott, ; Martin, Navne, & Lipczak, ; Ringdal, Chaboyer, Ulin, Bucknall, & Oxelmark, ; Skagerstrom, Ericsson, Nilsen, Ekstedt, & Schildmeijer, ).…”
Section: Introductionmentioning
confidence: 99%